LIFE DEDICATED TO SCIENCE (Scientific journal of the Fergana State University, 2024)
This article talks about the role of women in our society, the research of women and girls working in the field of science, and the analysis of the scientific and pedagogical work of Pulatova Manzura Iskhakovna, professor of the "Higher Mathematics" department of BukhMTI.